Evaluation of the Implementation of Strategic Human Resource Management (SHRM) on Organizational Performance in the Era of Digital Transformation - Supangat Supangat; Sugeng Marsudi (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study aims to evaluate the implementation of Strategic Human Resource Management (SHRM) on organizational performance in the era of digital transformation. Digital transformation has driven organizations to integrate technology, data, and innovation in human resource management to enhance competitiveness and business sustainability. The research method used is a quantitative approach with a survey design, involving respondents from various industrial sectors undergoing digitalization. Data were collected through structured questionnaires and analyzed using inferential statistical techniques to examine the relationship between SHRM practices such as digital-based HR planning, digital competency development, technology-based performance management, and adaptive organizational culture and organizational performance. The research results indicate that the implementation of SHRM integrated with digital technology has a positive and significant impact on improving organizational performance, both in terms of productivity, innovation, and operational effectiveness. Moreover, digital HR capabilities and transformational leadership support have proven to be key factors in strengthening that relationship. This research provides practical implications for organizations to design HR strategies that are adaptive to technological changes and strengthen the role of SHRM as a strategic partner in achieving competitive advantage in the digital era.